2011
DOI: 10.1242/jcs.076042
|View full text |Cite
|
Sign up to set email alerts
|

The human NKG2D ligand ULBP2 can be expressed at the cell surface with or without a GPI anchor and both forms can activate NK cells

Abstract: SummaryThe activating immune receptor NKG2D binds to several stress-induced ligands that are structurally different. MHC-class-I-related chain (MIC) A/B molecules have a transmembrane domain, whereas most UL16 binding proteins (ULBPs) are glycosylphosphatidylinositol (GPI)-linked molecules. The significance of this variability in membrane anchors is unclear. Here, we demonstrate that ULBP2, but not ULBP1 or ULBP3, can reach the cell surface without the GPI modification. Several proteins are expressed at the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…The ULBP1-3 molecules are all anchored to the plasma membrane via a glycosylphophatidylinositol (GPI) domain. However, it has been shown that ULBP2, but not ULBP1 and 3, can relocate to the cell surface in the absence of a GPI moiety as a transmembrane protein that allows for more stable interaction with NKG2D receptors on NK cells (28). Moreover, soluble levels of ULBP2 have been correlated with reduced survival in patients with cancer, which has not been shown for other NKG2D ligands (29).…”
Section: Discussionmentioning
confidence: 97%
“…The ULBP1-3 molecules are all anchored to the plasma membrane via a glycosylphophatidylinositol (GPI) domain. However, it has been shown that ULBP2, but not ULBP1 and 3, can relocate to the cell surface in the absence of a GPI moiety as a transmembrane protein that allows for more stable interaction with NKG2D receptors on NK cells (28). Moreover, soluble levels of ULBP2 have been correlated with reduced survival in patients with cancer, which has not been shown for other NKG2D ligands (29).…”
Section: Discussionmentioning
confidence: 97%
“…Human ULBP1–3 and 6 and mouse RAE1α–ε and H60c are GPI-linked, whereas human ULBP4–5 and mouse MULT1 and H60a and b are transmembrane proteins. In some cases (e.g., ULBP2 and possibly others), both GPI-linked and transmembrane forms of the protein are found on the same cell (22). The original image was kindly provided by Dr. Roland Strong of the Fred Hutchinson Cancer Research Center.…”
Section: Figurementioning
confidence: 99%
“…The RAET1 genes demonstrate less allelic polymorphism than the MICA and MICB genes. MICA, MICB, RAET1E (ULBP4), and RAET1G (ULBP5) are transmembrane-anchored glycoproteins, whereas RAET1I (ULBP1), RAET1H (ULBP2), RAET1N (ULBP3), and RAET1L (ULBP6) are glycophosphatidylinositol (GPI)-anchored, although RAET1H (ULBP2) may be expressed in both transmembrane-anchored and GPI-anchored forms (28) and RAET1G (ULBP5) may be GPI-anchored (29). Mice have orthologs of the human RAET1 genes present on mouse chromosome 10, but none of the mouse ligand genes correspond to MICA or MICB or are encoded within the mouse MHC.…”
Section: Nkg2d Ligand Genes and Proteinsmentioning
confidence: 99%